2020
DOI: 10.1037/cdp0000281
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with discrimination: Parents’ and adolescents’ racial discrimination experiences and parenting in African American families.

Abstract: Objectives: Survey data of 155 Midwestern African American adolescents (M age ϭ 13.25, 54.8% female) and their parents were assessed to examine whether parents' racial discrimination experiences and adolescents' gender moderated the association between adolescents' racial discrimination experiences and involved-vigilant parenting. Methods: Path analyses were conducted with racial discrimination and gender at Wave 1 predicting parenting at Wave 2, controlling for Wave 1 parenting and demographic variables. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…A growing body of research demonstrates that Black parents may experience significant distress resulting from their children's experiences of racial discrimination (Colen et al, 2019;Cooper et al, 2015Cooper et al, , 2019Gee et al, 2012;Murry, 2019;Murry et al, 2018;Varner et al, 2020). We built on this work to understand how Black fathers' own racial identity may moderate the relation between their perception of adolescents' experiences of racial discrimination and their own depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A growing body of research demonstrates that Black parents may experience significant distress resulting from their children's experiences of racial discrimination (Colen et al, 2019;Cooper et al, 2015Cooper et al, , 2019Gee et al, 2012;Murry, 2019;Murry et al, 2018;Varner et al, 2020). We built on this work to understand how Black fathers' own racial identity may moderate the relation between their perception of adolescents' experiences of racial discrimination and their own depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous research has documented that Black parents may differ in their expectations of how frequently their adolescent sons and daughters might experience racial discrimination, it remains unclear whether and how adolescent boys' and girls' actual discrimination experiences might influence their parents differently. Specifically, Varner et al (2020) found that parents engaged in less involvedvigilant parenting when they experienced little discrimination but had boys with more frequent discrimination experiences. This pattern did not exist for parents of girls or parents who had experienced high levels of discrimination.…”
Section: Black Fathers and Adolescent Gendermentioning
confidence: 99%
See 3 more Smart Citations